Pengaruh employer branding terhadap intention to apply job melalui corporate reputation (studi kasus pada departemen manajemen dan pengembangan sumber daya manusia di PT XYZ) - Nurul Silviatur Rohmania, (Jurnal Ilmu Manajemen, 2025)
This study aims to examine and analyze in depth the influence of Employer Branding on Job Application Intention, considering the role of Corporate Reputation as a mediating variable. This research was conducted on a case study in the Department of Human Resource Management and Development. The sampling technique used was saturated sampling, involving the entire population as respondents. The total number of respondents was 32 employees working in the Department of Human Resource Management and Development. This research was quantitative, with data analysis using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, processed and analyzed using SmartPLS software version 4.1. Based on the data processing results, it was found that employer branding did not significantly influence job application intention among the respondents involved in this study. Conversely, corporate reputation was found to have a positive and significant influence on job application intention, indicating that corporate image plays a crucial role in attracting applicants. Furthermore, the results also indicated that employer branding did not significantly influence corporate reputation. Indirect relationship testing revealed that employer branding was unable to mediate the relationship between employer branding itself and job application intentions. Overall, these findings suggest that efforts to build a company's reputation have a more significant impact than relying solely on employer branding strategies in influencing job application intentions.